Pengaruh Utang Jangka Pendek terhadap Laba Bersih PT. XL Axiata Tbk Tahun 2019-2021 - Khoifulloh, Muhammad; Gastri Widjamiko, Andrik; Aini Anisa, Nur (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2025)
The establishment of a company basically has a purpose. One of these goals is to continue to progress and develop. To see the development of a company can be seen in terms of the profits achieved by the company, namely profit, where profit is important in a company. Researchers are interested in examining the profit and short-term debt of PT XL Axiata Tbk because in the 2019-2021 interval, the company collaborated with the government in providing free quotas for students, which resulted in sales profits unlike the previous year, where internet quota sales were unstable due to quota subsidies from the government. This study aims to determine the magnitude of the effect of short-term debt on net income at PT XL Axiata Tbk. The method used is a quantitative method. The analysis sample in this study is the quarterly financial reports of PT XL Axiata Tbk listed on the IDX from 2019-2021. To determine its influence, statistical tests were used, namely simple linear regression analysis, correlation analysis, and hypothesis testing (t-test) as well as determination analysis (R2). The results of this study can be seen the effect of short-term debt as an independent variable partially on profit as a dependent variable, which shows that the significance value of the short-term debt variable is 0.067, which is greater than 0.05. This indicates that short-term debt has no effect on net profit. It can also be seen that the determination coefficient value (R2) is 0.296 or 29.6%. This shows the effect of short-term debt on net profit is 29.6% while the remaining 70.4% is influenced by other variables not included in this model.